2001
DOI: 10.1007/s003300101066
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysms of saphenous vein grafts as late complication of coronary artery bypass surgery: successful exclusion by percutaneous transcatheter embolization

Abstract: We report a case of a 71-year-old man with a long coronary artery disease history and two sets of coronary artery bypass grafts. He developed large aortocoronary saphenous vein graft aneurysms in the two grafts from the first set of aortocoronary saphenous venous 20 years later. During the previous 3 years, the aneurysms grew in diameter from 22 to 50 mm. Because of severe renal insufficiency, and in order to avoid jeopardizing the late normal coronary artery bypass grafts by further thoracic surgery, we exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Our literature review identified 107 patients [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95]. The demographic, clinical and pathological features are summarized in ...…”
Section: Resultsmentioning
confidence: 99%
“…Our literature review identified 107 patients [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95]. The demographic, clinical and pathological features are summarized in ...…”
Section: Resultsmentioning
confidence: 99%
“…Previous reports have described the use of the Graftmaster covered stent, which is composed of two layers of stent with a PTFE graft between the stents. This device is bulky and potentially problematic to deliver . New versions of covered stent, such as the Papyrus (Biotronik, Berlin, Germany), which utilizes a single layer of polyurethane, and BeStent (Bentley Innomed, Hechingen, Germany), with a single layer of stent struts, are considerably more deliverable, may be delivered through a 5 Fr sheath and ideally suited to vein graft aneurysm intervention up to a size of 5.5 mm when using standard PCI equipment over a 0.018″ guidewire (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Embolization or stenting of the aneurysms is another treatment option [10,11]. Unfortunately, our patient deteriorated rapidly to provide the surgical treatment he needed.…”
Section: Discussionmentioning
confidence: 99%